Could early tumour volume changes assessed on morphological MRI predict the response to chemoradiation therapy in locally-advanced rectal cancer?. Issue 6 (June 2018) - Palmisano, A.; Esposito, A.; Di Chiara, A.; Ambrosi, A.; Passoni, P.; Slim, N.; Fiorino, C.; Albarello, L.; Di Muzio, N.; Calandrino, R.; Rosati, R.; Del Maschio, A.; et al.
Abstract : Aim: To investigate the potential role of an additional magnetic resonance imaging (MRI) examination performed during neoadjuvant chemoradiation therapy (CRT) in the prediction of pathological response in locally advanced rectal cancer (LARC). Material and methods: Forty-eight consecutive patients with LARC underwent neoadjuvant CRT. MRI studies at 1.5 T, including high-resolution T2-weighted sequences that were acquired parallel and perpendicular to the main axis of the tumour were performed before (preMRI), during (midMRI), and 6–8 weeks after the end of CRT (postMRI). Cancer volumes (Vpre, Vmid, Vpost ) were drawn manually and the reduction rate calculated (ΔVmid, ΔVpost ). According to Rödel's pathological tumour regression grade (TRG), patients were considered non-responders (NR; TRG0-2), partial responders (PR; TRG3), and complete responders (CR; TRG4). Multivariate regression analysis was performed to identify the best MRI predictors of NR, PR, and CR. Results: Twenty-five patients were considered PR (52%), 13 CR (27%), and 10 NR (22%). Tumour shrinkage mainly occurred shortly after CRT (ΔVmid : CR: 80±10% versus PR: 56±19% versus NR: 28±22%, p= 2.2×10 −16 ). Vmid, Vpost, ΔVmid, and ΔVpost correlated with TRG ( p< 0.001). At multivariate analysis, the combined assessment of Vmid and ΔVmid was selected as the best predictor of response to CRT, in that it distinguishes CR, PR, and NR early and accurately (81.5%). Conclusion: MidMRI allows final response assessment to neoadjuvant CRT earlier and better than the MRI performed after the end of CRT. MRI findings at midMRI may be useful to tailor patient treatment. Highlights: An additional MRI performed during CRT may be useful in the early evaluation of response to CRT. TRG correlated slightly better with ΔVmid (ρ=0.713, p<0.001) than ΔVpost (ρ=0.645, p<0.001). MidMRI might be potentially useful to tailor patient's treatment in relation to tumour shrinkage.